Knowledge, curriculum and equity: social realist perspectives - Barrett, Brian, 1978-; Hoadley, Ursula; Morgan, John (Palgrave studies in excellence and equity in global education, 2020)
"Knowledge and the Future of the Curriculum: International Studies in Social Realism is about the central purpose of schooling - to provide students with equitable access to powerful curriculum knowledge that is ultimately capable of taking them beyond their experiences. This collection presents a social realist understanding of the role of knowledge as a progressive option in support of social and educational justice. It moves beyond mere critique by offering a rationale for determining what should be taught and how it should be taught. It is an account justified by a theory of knowledge that acknowledges both its social location and its emergent and objective properties. Each chapter argues in creative and innovative ways for a curriculum and pedagogy that will enable all students to access powerful knowledge"--